2004
DOI: 10.1093/jac/dkh071
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Candida albicans biofilms grown in a constant depth film fermentor to chlorhexidine, fluconazole and miconazole: a longitudinal study

Abstract: We have shown in this study that the susceptibility of C. albicans to antifungal and antimicrobial agents changes throughout biofilm development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 9 publications
5
60
0
8
Order By: Relevance
“…Similarly, another study has reported the superior efficacy of chlorhexidine gluconate (0.12%) and Listerine mouthwashes in eliminating Candida biofilms [116]. Interestingly, in a flow biofilm model of C. albicans, chlorhexidine appeared to be more effective in comparison to fluconazole and miconazole in reducing biofilm Candida [117].…”
Section: Mouth Washesmentioning
confidence: 88%
“…Similarly, another study has reported the superior efficacy of chlorhexidine gluconate (0.12%) and Listerine mouthwashes in eliminating Candida biofilms [116]. Interestingly, in a flow biofilm model of C. albicans, chlorhexidine appeared to be more effective in comparison to fluconazole and miconazole in reducing biofilm Candida [117].…”
Section: Mouth Washesmentioning
confidence: 88%
“…As ergosterol is an important constituent of the cytoplasmic membrane, treatment with azole antifungals leads to growth inhibition (31). Besides this fungistatic mechanism of action, recent data indicate a fungicidal effect of miconazole (an imidazole) against Candida species cells in suspension and in young and mature biofilms (17,28). The accumulation of reactive oxygen species appears to be involved in this process, although it is likely that other mechanisms are also involved in the fungicidal activity (10,16,27).…”
mentioning
confidence: 99%
“…Given that C. albicans within a biofilm can be up to 1,000-fold more resistant than planktonic yeast to fluconazole (31,32), and given the specificity of xanthochymol for hyphae, we tested whether the two compounds might have complementary antifungal activities. We tested the combination of fluconazole and xanthochymol at 3 h and 24 h of biofilm development.…”
Section: Resultsmentioning
confidence: 99%